2018
DOI: 10.1534/genetics.118.301736
|View full text |Cite
|
Sign up to set email alerts
|

Robust CRISPR/Cas9-Mediated Tissue-Specific Mutagenesis Reveals Gene Redundancy and Perdurance inDrosophila

Abstract: Tissue-specific loss-of-function (LOF) analysis is essential for characterizing gene function. Here, we present a simple, yet highly efficient, clustered regularly interspaced short palindromic repeats (CRISPR)-mediated tissue-restricted mutagenesis (CRISPR-TRiM) method for ablating gene function in Drosophila. This binary system consists of a tissue-specific Cas9 and a ubiquitously expressed multi-guide RNA (gRNA) transgene. We describe convenient toolkits for making enhancer-driven Cas9 lines and multi-gRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(133 citation statements)
references
References 53 publications
8
125
0
Order By: Relevance
“…Toxicity mediated by high levels of Cas9 have been previously described by us and others in Drosophila and have also been observed in various other species (Port et al, 2014;Yang et al, 2018;Jiang et al, 2014;Poe et al, 2019). It has recently been reported that Cas9 transgenic lines directly fused to tissue-specific enhancers can mediate conditional mutagenesis with reduced toxicity (Poe et al, 2019). However, the UAS-uCas9 system reported here has several advantages, such as the ability to harness the thousands of publicly available tissue-specific Gal4 lines, the possibility to modulate Cas9 expression levels independent of enhancer strength, or the availability of the temperature-sensitive Gal4 repressor Gal80 for additional temporal control of gene editing.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Toxicity mediated by high levels of Cas9 have been previously described by us and others in Drosophila and have also been observed in various other species (Port et al, 2014;Yang et al, 2018;Jiang et al, 2014;Poe et al, 2019). It has recently been reported that Cas9 transgenic lines directly fused to tissue-specific enhancers can mediate conditional mutagenesis with reduced toxicity (Poe et al, 2019). However, the UAS-uCas9 system reported here has several advantages, such as the ability to harness the thousands of publicly available tissue-specific Gal4 lines, the possibility to modulate Cas9 expression levels independent of enhancer strength, or the availability of the temperature-sensitive Gal4 repressor Gal80 for additional temporal control of gene editing.…”
Section: Discussionsupporting
confidence: 59%
“…The small amount of Cas9 that is needed for efficient gene editing allows expression of Cas9 at low levels, which avoids toxicity without sacrificing on-target activity. Toxicity mediated by high levels of Cas9 have been previously described by us and others in Drosophila and have also been observed in various other species (Port et al, 2014;Yang et al, 2018;Jiang et al, 2014;Poe et al, 2019). It has recently been reported that Cas9 transgenic lines directly fused to tissue-specific enhancers can mediate conditional mutagenesis with reduced toxicity (Poe et al, 2019).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We designed three sets of gRNAs targeting trpm (see Materials and Methods). We used the "Cas9-LEThAL" (24) method to evaluate the efficiency of our gRNA expression constructs. Among them, gRNA set 3 displayed the highest efficiency (Table.S1).…”
Section: Germline Specific Crispr/cas9 Knockout Of Trpm Inhibits Calcmentioning
confidence: 99%
“…To confirm the efficiency of constructs expressing gRNAs, we employed the "Cas9-LEThAL" method (24) to validate the efficiency of our gRNA constructs. Males carrying gRNA constructs were crossed to act-Cas9, lig4-mutant females.…”
Section: Grna Construct Efficiency Testmentioning
confidence: 99%